2023
DOI: 10.1038/s41467-023-36106-x
|View full text |Cite
|
Sign up to set email alerts
|

Shark nanobodies with potent SARS-CoV-2 neutralizing activity and broad sarbecovirus reactivity

Abstract: Despite rapid and ongoing vaccine and therapeutic development, SARS-CoV-2 continues to evolve and evade, presenting a need for next-generation diverse therapeutic modalities. Here we show that nurse sharks immunized with SARS-CoV-2 recombinant receptor binding domain (RBD), RBD-ferritin (RFN), or spike protein ferritin nanoparticle (SpFN) immunogens elicit a set of new antigen receptor antibody (IgNAR) molecules that target two non-overlapping conserved epitopes on the spike RBD. Representative shark antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…To combat the pandemic, researchers have sought to develop antibodies against the SARS-CoV-2 receptor binding domain (RBD) for use in viral therapeutics and diagnostics [ 2 , 3 ], including single-domain antibodies (sdAbs). SdAbs are antibody fragments of heavy chain-only antibodies derived from camelid IgG2 and IgG3 [ [4] , [5] , [6] , [7] , [8] , [9] , [10] ], or cartilaginous fish immunoglobulin new antigen receptor (IgNAR) [ [11] , [12] , [13] , [14] , [15] , [16] ]. SdAbs obtained from camelids or cartilaginous fishes are known as nanobodies or VNARs, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To combat the pandemic, researchers have sought to develop antibodies against the SARS-CoV-2 receptor binding domain (RBD) for use in viral therapeutics and diagnostics [ 2 , 3 ], including single-domain antibodies (sdAbs). SdAbs are antibody fragments of heavy chain-only antibodies derived from camelid IgG2 and IgG3 [ [4] , [5] , [6] , [7] , [8] , [9] , [10] ], or cartilaginous fish immunoglobulin new antigen receptor (IgNAR) [ [11] , [12] , [13] , [14] , [15] , [16] ]. SdAbs obtained from camelids or cartilaginous fishes are known as nanobodies or VNARs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…SdAbs possess several advantageous properties that make them attractive for use in therapeutics and diagnostics, including small size, high physicochemical stability, solubility, specificity for cryptic epitopes, low immunogenicity, ease of protein engineering, more efficient cell penetration, and low production cost [ 17 , 18 ]. Because of these advantages, some researchers have attempted to develop multivalent [ 6 , 14 , 16 ] or nasal drugs [ 7 ] using SARS-CoV-2 RBD-specific sdAbs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent research has shown that other animals also have similar strategies to diversify their antibodies. For example, sharks produce a type of antibody called IgNAR (Variable domain of the immunoglobulin new antigen receptor) that is also small and stable like nanobodies [11] . Additionally, some rodents have been found to produce single-domain antibodies similar to nanobodies [12] .…”
Section: Introductionmentioning
confidence: 99%
“…The production of nanobodies or similar antibodies in different animals involves a complex process of genetic rearrangement and selection. In camels and llamas, for example, the genes encoding the heavy chain of their antibodies undergo a unique process called VHH gene rearrangement that leads to the production of nanobodies [13] In sharks, IgNAR antibodies are produced by a different mechanism involving gene conversion and somatic hypermutation [11] . Similarly, rodents use a process called VHH gene conversion to produce single-domain antibodies [13] .…”
Section: Introductionmentioning
confidence: 99%